Norovirus-VLPs expressing pre-erythrocytic malaria antigens induce functional immunity against sporozoite infection. Issue 31 (29th July 2022) - Schneider, Cosette G.; Fey, Julien; Zou, Xiaoyan; Gerbasi, Vince; Savransky, Tatyana; Batt, Carl; Bergmann-Leitner, Elke; Angov, Evelina
Abstract: Despite the development of prophylactic anti-malarial drugs and practices to prevent infection, malaria remains a health concern. Preclinical testing of novel malaria vaccine strategies achieved through rational antigen selection and novel particle-based delivery platforms is yielding encouraging results. One such platform, self-assembling virus-like particles (VLP) is safer than attenuated live viruses, and has been approved as a vaccination tool by the FDA. We explore the use of Norovirus sub-viral particles lacking the natural shell (S) domain forming the interior shell but that retain the protruding (P) structures of the native virus as a vaccine vector. Epitope selection and their surface display has the potential to focus antigen specific immune responses to crucial epitopes. Recombinant P-particles displaying epitopes from two malaria antigens, Plasmodium falciparum (Pf) CelTOS and Plasmodium falciparum (Pf) CSP, were evaluated for immunogenicity and their ability to confer protection in a murine challenge model. Immune responses induced in mice resulted either in sterile protection (displaying PfCelTOS epitopes) or in antibodies with functional activity against sporozoites (displaying PfCSP epitopes) in an in vitro liver-stage development assay (ILSDA). These results are encouraging and support further evaluation of this platform as a vaccine delivery system.